New insights into cooked rice quality by measuring modulus, adhesion and cohesion at the level of an individual rice grain. (January 2019) - Yu, L.; Witt, T.; Rincon Bonilla, M.; Turner, M.S.; Fitzgerald, M.; Stokes, J.R.
Abstract: Causal relationships between physical properties and structure/composition of cooked rice are difficult to quantify when mechanical measurements are performed on bulk samples using large deformations that alter the structure irreversibly. We demonstrate here methods involving small-deformation to characterise the elastic modulus ( E ), adhesion and cohesion at the individual grain level, and show distinct differences between freshly cooked rice and shelf-stable retorted rice. On average, retorted rice is harder and less adhesive and cohesive than freshly cooked rice, but their distributions in each of these mechanical properties overlap. E is independent of adhesion and weakly correlated with moisture content. In addition, a ring-shear tester is shown to distinguish the bulk cohesion and flowing ability between rice samples. Measuring the inherent physical properties of individual grains has the potential to enable a more sensitive evaluation of new processes and grain varieties, and development of quantitative structure-property-processing relationships for rational design of products to perform optimally at different stages, from manufacturing through to oral processing. Highlights: Inherent physical properties of individual rice grains are characterized instrumentally. Distributions of mechanical properties of individual freshly cooked and retorted rice grains overlap. Adhesion and cohesion of rice grains are measured as surface properties. Elastic modulus is independent from adhesion and weakly correlated with moisture content. New method developed to distinguish bulk cohesion of rice with a ring shear tester.